2014
DOI: 10.1136/jnnp-2013-306799
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic flow chart forPOLG-related diseases based on signs sensitivity and specificity

Abstract: Phenotypes associated with POLG mutations follow a reproducible pattern, which allows establishing a diagnostic flow chart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…Three patients (patient 1, 4 and 5) had a history of migraine but in one of these three patients, genetic testing showed that migraine did not co-segregate with the mutation in his family. Six of our patients had sensory axonal polyneuropathy which is in line with the high percentage of 94 % reported in a recent paper of Tchikviladze et al [29]. In our cohort, no patient showed psychiatric comorbidity [29,30].…”
Section: Additional Clinical Featuressupporting
confidence: 90%
See 1 more Smart Citation
“…Three patients (patient 1, 4 and 5) had a history of migraine but in one of these three patients, genetic testing showed that migraine did not co-segregate with the mutation in his family. Six of our patients had sensory axonal polyneuropathy which is in line with the high percentage of 94 % reported in a recent paper of Tchikviladze et al [29]. In our cohort, no patient showed psychiatric comorbidity [29,30].…”
Section: Additional Clinical Featuressupporting
confidence: 90%
“…Six of our patients had sensory axonal polyneuropathy which is in line with the high percentage of 94 % reported in a recent paper of Tchikviladze et al [29]. In our cohort, no patient showed psychiatric comorbidity [29,30].…”
Section: Additional Clinical Featuressupporting
confidence: 90%
“…Mutations of the mitochondrial DNA (mtDNA) encoded by the POLG gene are an important cause of pediatric and adult-onset mitochondrial disease. In adults, they are associated with multiple mtDNA deletions leading to a wide spectrum of dominant and recessive progressive neurological disorders, often described as syndromes, such as progressive external ophthalmoplegia, Alpers syndrome, sensory ataxic neuropathy, dysarthria and ophthalmoparesis (65, 66). POLG mutation should also be considered in patients with PAPT or progressive ataxia with inferior olive hypersignal (54), even in sporadic cases, and even without other frequently associated neurological signs such as sensory neuronopathy associated with weakness of ocular, pharyngeal, axial, and/or limb muscles (66).…”
Section: Etiologiesmentioning
confidence: 99%
“…They are the most common monogenic cause of inherited autosomal mitochondrial disease. Their wide clinical phenotype spectrum ranges ABBREVIATIONS: ADA, adenosine deaminase; dAdo, deoxyadenosine; dATP, dAdo triphosphate; dCtd, deoxycytidine; dCTP, dCtd triphosphate; dGTP, dGuo triphosphate; dGuo, deoxyguanosine; dIno, deoxyinosine; dN, deoxyribonucleoside; dNTP, deoxyribonucleoside triphosphate; dThd, deoxythymidine; dTTP, dThd triphosphate; dUrd, deoxyuridine; EHNA, erythro-9-(2-hydroxy-3-nonyl) adenine; EtBr, ethidium bromide; FBS, fetal bovine serum; mip1, DNA-directed DNA polymerase g; mtDNA, mitochondrial DNA; PDB, Protein Data Bank; PEO, progressive external ophtalmoplegia; POLG, polymerase g catalytic subunit; TK2, thymidine kinase 2 from severe infantile to mild adult-onset manifestations (4,5). Infantile forms include Alpers-Huttenlocher syndrome and myohepatocerebral syndromes.…”
mentioning
confidence: 99%